Medicinal Properties of Tamarind Seeds: A Mini Review (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Tamarind seeds, scientifically known as Tamarindus indica L., has been found to possess notable antimicrobial effects making them a potential source for combating microbial infections. The unique phytochemical composition of tamarind seeds contributes to their antimicrobial activity. These compounds effectively inhibit the growth of various pathogenic bacteria and fungi, highlighting their potential in combating antimicrobial resistance. This review explores how tamarind seeds could serve as a new ingredient with medicinal properties.
Keywords: Tamarindus indica L; Tamarind; Seeds; Infection; Antimicrobial resistance